An intraocular eyelash after uneventful cataract surgery - Francis Stanley, Philip (Am J Ophthalmol Case Rep, 2020)
PURPOSE: The finding of an anterior chamber cilium after small incision cataract surgery is rare, with only five prior cases being found on literature review. Strategies include observation if there is no evidence of inflammation or infection and prompt removal if the situation changes.1-5 This case adds to the number of case reports and highlights that unexpected findings such as this can be seen on the first postoperative day exam and the clinical decisions made to remove it promptly. OBSERVATIONS: A 69 year-old woman had uncomplicated phacoemulsification cataract extraction with posterior chamber intraocular lens implantation in the right eye using a superonasal corneal incision and inferotemporal paracentesis. Examination at 1 day noted a cilium in the anterior chamber. The cilium was removed the same day without complications. CONCLUSIONS AND IMPORTANCE: This case report shows that intraocular cilia can occasionally be seen following routine small incision sutureless cataract surgery even when there is no evidence of it immediately following surgery.